Functional Genomic Screening During Somatic Cell Reprogramming Identifies DKK3 as a Roadblock of Organ Regeneration. Issue 14 (13th May 2021) - Arnold, Frank; Mahaddalkar, Pallavi U; Kraus, Johann M.; Zhong, Xiaowei; Bergmann, Wendy; Srinivasan, Dharini; Gout, Johann; Roger, Elodie; Beutel, Alica K.; Zizer, Eugen; Tharehalli, Umesh; Daiss, Nora; et al.
Abstract: Somatic cell reprogramming and tissue repair share relevant factors and molecular programs. Here, Dickkopf‐3 (DKK3) is identified as novel factor for organ regeneration using combined transcription‐factor‐induced reprogramming and RNA‐interference techniques. Loss of Dkk3 enhances the generation of induced pluripotent stem cells but does not affect de novo derivation of embryonic stem cells, three‐germ‐layer differentiation or colony formation capacity of liver and pancreatic organoids. However, DKK3 expression levels in wildtype animals and serum levels in human patients are elevated upon injury. Accordingly, Dkk3 ‐null mice display less liver damage upon acute and chronic failure mediated by increased proliferation in hepatocytes and LGR5 + liver progenitor cell population, respectively. Similarly, recovery from experimental pancreatitis is accelerated. Regeneration onset occurs in the acinar compartment accompanied by virtually abolished canonical‐Wnt‐signaling in Dkk3 ‐null animals. This results in reduced expression of the Hedgehog repressor Gli3 and increased Hedgehog‐signaling activity upon Dkk3 loss. Collectively, these data reveal Dkk3 as a key regulator of organ regeneration via a direct, previously unacknowledged link between DKK3, canonical‐Wnt‐, and Hedgehog‐signaling. Abstract : Re‐activation of embryonic pathways is a hallmark of tissue repair after injury. During somatic reprogramming similar molecular patterns are re‐activated, thus providing an excellent platform to identify relevant factors in tissue repair. Here, Dickkopf‐3 (DKK3) is identified as key player of gastrointestinal tissue regeneration and repair via a DKK3‐mediated interplay of canonical Wnt‐ and Hedgehog‐signaling.